2012
DOI: 10.1007/s11999-011-2229-8
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopically Determined Degree of Injury After Shoulder Dislocation Relates to Recurrence Rate

Abstract: Background The glenohumeral joint is the most mobile articulation in the body and the most commonly dislocated diarthrodial joint with peaks in the incidence of dislocation occurring during the second and sixth decades. Age at the time of the initial dislocation is inversely related to the recurrence rate. Traumatic anterior instability is often associated with intraarticular injuries. The frequency of injuries may increase with dislocation or subluxation episodes. Questions/purposes We compared the frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 16 publications
0
22
2
1
Order By: Relevance
“…They proposed a progressive degenerative process of the labrum-ligament complex, which correlated with number of recurrences. Gutierrez et al 20 retrospectively compared intra-articular findings in 45 first-time dislocators and 51 recurrent dislocators who underwent arthroscopy. They found a higher incidence of SLAP tears and rotator cuff tears among recurrent dislocators.…”
Section: Discussionmentioning
confidence: 99%
“…They proposed a progressive degenerative process of the labrum-ligament complex, which correlated with number of recurrences. Gutierrez et al 20 retrospectively compared intra-articular findings in 45 first-time dislocators and 51 recurrent dislocators who underwent arthroscopy. They found a higher incidence of SLAP tears and rotator cuff tears among recurrent dislocators.…”
Section: Discussionmentioning
confidence: 99%
“…At each recurrence, passing lesions are exacerbated, with labral damage, capsule stretching and glenoid bone lesions and notching [52,53], reducing the chances of successful arthroscopic stabilization. Samilson and Prieto were the first to introduce the notion of shoulder osteoarthritis induced by instability [54].…”
Section: Discussionmentioning
confidence: 99%
“…Due the presence of the rotator cuff muscles both Palastanga et al (2006) and Sinnatamby (2006) assume that anterior dislocation of the shoulder is not common. However, Cutts et al (2009), Bankart (1923), Ufberg et al (2004), Chechik et al (2011) and Gutierrez et al (2012) disagree stating that as the shoulder joint is the most mobile joint in the body anterior dislocation accounts for the majority of dislocations and occur predominately in males. The current study found that females were significantly more likely to have a type I or II glenoid notch and males significantly more likely to have a type III glenoid notch.…”
Section: Crosstabmentioning
confidence: 99%
“…The peak incidence of shoulder joint dislocation occurs between 20 and 60 years of age. Anterior dislocation accounts for the majority of shoulder dislocations which predominately occur in males (Milgrom et al, 2014;Cutts et al, 2009;Bankart, 1923;Ufberg et al, 2004;Chechik et al, 2011;Gutierrez et al, 2012). The recurrence rate of anterior glenohumeral dislocation after initial dislocation in young athletes is between 54% and 92% (Wheeler et al, 1989;Bottoni et al, 2002;Te Slaa et al, 2003;Jakobsen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%